Evaluation of documented information (ISO 9001: 2015 standard): Conventional bioteries in Venezuela - Moya Acosta, Manuel Jesús; Barreto, Michel; Goncalves , Irene; Morales, Ángela (Spei Domus, 2023)
To assure the quality of work with laboratory animals, it is essential to standardize their breeding and maintenance processes. The ISO 9001:2015 standard meets the requirements that certify the Quality Management Systems of an organization. The work focuses primarily on the establishment and evaluation of documented information of the processes referred to in requirement 7.5 of ISO 9001: 2015; this regulatory requirement is part of a management system that focuses on customer satisfaction with respect to meeting their needs. A descriptive and exploratory research was conducted. An instrument (survey) was designed where information was collected on the use of documentation in production and experimental processes. 22 conventional bioterias registered in the Asociación Venezolana para la Ciencia de Animales de Laboratorio (avecal) were studied. The instrument was sent via email to the Heads of each one of the Bioterias. Data were collected and tabulated according to the variables investigated. It was evidenced that 81.8% of these bioterias do not have documents that allow a control and monitoring of their processes. Likewise, those responsible are unaware of the national legal framework, such as the Ley Orgánica del Sistema Venezolano para la Calidad, Normas Generales de Control Interno de la Contraloría General de la República and the ISO 9001:2015. The design of a methodological guide is recommended, so that national bioterias prepare their documents following clause 7.5 of the ISO 9001: 2015 standard to improve the efficiency of their processes.